2015
DOI: 10.1016/j.thromres.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of protein C and factor VIII in prediction of cancer-associated thrombosis

Abstract: Venous thromboembolism (VTE) is a preventable disease, yet it is one of the leading causes of death among patients with cancer. Improving risk stratification mechanisms will allow us to personalize thromboprophylaxis strategies. We sought to evaluate Collagen and Thrombin Activated Platelets (COAT-platelets) as well as protein C and factor VIII as biomarkers predictive of cancer-associated thrombosis in a prospective cohort of patients with cancer. Protein C was selected as a candidate based on bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
1
13
0
2
Order By: Relevance
“…Similarly, FVIII has shown prospective predictive potential in a subset of adults, both in association with CVC and without CVC (adjusted OR = 3), with FVIII levels >200%. None of these studies evaluated the value of combining clinical prediction tools and biomarkers, but several compared the two approaches in the evaluation of at‐risk adults …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, FVIII has shown prospective predictive potential in a subset of adults, both in association with CVC and without CVC (adjusted OR = 3), with FVIII levels >200%. None of these studies evaluated the value of combining clinical prediction tools and biomarkers, but several compared the two approaches in the evaluation of at‐risk adults …”
Section: Discussionmentioning
confidence: 95%
“…Several adult studies demonstrated the association of elevated TG parameters with the occurrence of the first VTE event (OR = 1.7) and with recurrence of unprovoked VTE (ORs = 1.6‐4.6) . Similarly, FVIII has shown prospective predictive potential in a subset of adults, both in association with CVC and without CVC (adjusted OR = 3), with FVIII levels >200%. None of these studies evaluated the value of combining clinical prediction tools and biomarkers, but several compared the two approaches in the evaluation of at‐risk adults …”
Section: Discussionmentioning
confidence: 99%
“…In addition, procoagulant phospholipids (PPL), i.e. anionic phospholipids, mainly phosphatidylserine, and a high level of coagulation factor VIII (FVIII), which is an acute-phase protein, have been associated with an increased risk of thrombosis [17,18] also including cancer patients [7,[19][20][21][22]. PPL is also present on the surface of EVs in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…10 It is reported that increased FVIII activity was a risk factor for venous thrombosis, and plasma activity of FVIII is mainly affected by genetic polymorphisms. 11 The major role of coagulation factor IX (factor X, FXA) in the coagulation process is to maintain the generation of thrombin and inhibition of fibrinolysis. 12 It is reported that people with high levels of FXI (10%) had 2.2-fold increased risk of DVT, compared with other people (90%).…”
Section: Introductionmentioning
confidence: 99%